2008
DOI: 10.1093/brain/awn183
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of neurological syndromes associated with glutamic acid decarboxylase antibodies: diagnostic clues for this association

Abstract: The association of high levels of autoantibodies to glutamic acid decarboxylase (GAD-ab) and stiff-person syndrome (SPS) is well known. However, the full spectrum of neurological syndromes associated with GAD-ab is not well established. In addition, these patients usually present type 1 diabetes mellitus (DM1) that could justify the presence of high GAD-ab levels. To clarify these issues, we reviewed the clinical and immunological features of patients in whom high GAD-ab levels were detected in a reference cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
529
2
19

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 554 publications
(577 citation statements)
references
References 57 publications
27
529
2
19
Order By: Relevance
“…A similar situation occurs in patients with glutamic acid decarboxylase (GAD)-ab. Patients with high titers of GAD-ab may develop stiff-man syndrome or cerebellar ataxia and postmortem studies show neuronal loss only in those with cerebellar ataxia (Ishida et al, 2007;Saiz et al, 2008). Taken together, these data suggest that when antibodies target cerebellar antigens, the functional impairment of the synaptic activity may lead to irreversible neuronal loss, a feature that is uncommon in other antibody-mediated neurological syndromes probably also mediated by antibodies targeting brain areas different from the cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…A similar situation occurs in patients with glutamic acid decarboxylase (GAD)-ab. Patients with high titers of GAD-ab may develop stiff-man syndrome or cerebellar ataxia and postmortem studies show neuronal loss only in those with cerebellar ataxia (Ishida et al, 2007;Saiz et al, 2008). Taken together, these data suggest that when antibodies target cerebellar antigens, the functional impairment of the synaptic activity may lead to irreversible neuronal loss, a feature that is uncommon in other antibody-mediated neurological syndromes probably also mediated by antibodies targeting brain areas different from the cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…To prove a causal link between GAD autoimmunity and the neurological syndrome, determination of the level of GAD-antibodies in cerebrospinal fluid (CSF) is necessary to confirm intrathecal synthesis. 2 In the patient reported by Akman et al, GAD-antibody levels were about 200-fold the upper limit of normal values in serum and CSF, which to the authors suggested a causal relationship between these antibodies and the neurological symptoms. As the CSF ⁄ serum antibody-index is not mentioned in their report, intrathecal antibody synthesis cannot be shown in this patient.…”
mentioning
confidence: 88%
“…Recently four patients with non-paraneoplastic limbic encephalitis associated with anti-GAD antibodies were reported. 2,3 Differentiation between autoimmune limbic encephalitis and paraneoplastic limbic encephalitis is important because the former is less frequently associated with cancer and often responds well to immunotherapy.…”
mentioning
confidence: 99%
“…A low positive result would suggest that these individuals are predisposed to or have Type I diabetes mellitus. However, these titres are not considered high enough to have a neurological impact (Saiz et al 2008;Liimatainen et al 2010). None of the GINMD or UK healthy control sera were positive UK.HC = UK healthy controls, SID = severe intestinal dysmotility B.HC = Brazilian healthy controls.…”
Section: Glutamic Acid Decarboxylasementioning
confidence: 99%
“…Data regarding stage of disease at diagnosis in the study of Kraichely et al are not provided. It should be mentioned that none of the positive anti-GAD sera, which were detected using an indirect immunofluorescence assay, were confirmed using the radioimmunoprecipitation assay to confirm specificity (Saiz et al 2008). …”
Section: Significance and Interpretationsmentioning
confidence: 99%